How occupational employment is affected by mass layoffs. - Itkin, Dina; Salmon, Laurie (Monthly Labor Review, 2011)
An analysis of business establishment microdata -- created by combining microdata from the Occupational Employment Statistics program and the Mass Layoff Statistics program -- reveals that jobs lost between 2000 and 2007 in establishments where extended mass layoffs occurred tended to be those which required less training and fewer analytical skills; jobs in occupations that were core to the specific industry generally were retained